(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2015)
This research aims to study the effect of laser surface treatment on wear resistance of different aluminum alloys (5086H32,6061-T).The specimens were hardened by using pulse Nd:YAG laser with wave length 1064 nm and pulse duration 100 ns with constant energy 1J and spot size1–5mm .Wear behavior of the specimens as –received and specimens treated by laser being studied by using pin-on-disc technique under dry sliding wear conditions at different applied loads and different sliding speeds.This study shows that the wear rate increases by increasing values of applied loads and decreases with increasing sliding speed, and wear rate for 6061-T6 alloy is less than 5086-H32 alloy. Also the results show that the micro hardness decreases by increasing hardening depth and the micro hardness values for 6061-T6 alloy more than 5086-H32 alloy at the same depth.